Construction of Regional Head Elections according to Article 18 Paragraph 4 of the 1945 Constitution Based on Popular Sovereignty - Nur, Ahmad Saripudin; Wibowo, Gatot Dwi Hendro; Zunnuraeini (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This study aims to analyze the historical development of regional elections in Indonesia, as well as to find ideal arrangements related to the construction of regional head elections according to Article 18 paragraph 4 of the 1945 Constitution based on popular sovereignty. The method used in this research is normative legal research using a statutory approach, conceptual approach, historical approach and comparative approach. The results of this study indicate that the arrangements related to regional head elections in Indonesia have undergone several changes in three historical periods, namely in the old order, new order and reform order periods. The changes are mainly concerned with the election model, where during the old order and new order the regional heads were appointed by the President, but during the reform order the regional heads were directly elected by the people. The ideal model for the election of regional heads based on popular sovereignty is that the Governor as the head of the provincial region should be carried out through democratic representation by the DPRD while the Regent/Mayor remains by direct election. This is related to the different principles of governance, the location of regional autonomy and budget efficiency in regional head elections.